The refusal of politics - Dubreuil, Laurent; Browning, Cory (Edinburgh : Edinburgh University Press, 2016)
Dubreuil provocatively proposes an extremist rethinking of the limits of politics ́⁰₃ toward a break from politics, the political and policies. He calls for a refusal of politics, suggesting a form of apolitics that would make our lives more liveable. The first chapter situates the refusal of politics in relation to different contemporary theoretical attempts to renew politics, and makes the case for a greater rupture. The second moment takes up what is liveable in life by way of apolitical experience, in contrast to appropriations of the collective, including a discussion of the arts. Finally, Laurent Dubreuil draws up an incomplete inventory of means, forms of existence ́⁰₃ often frail and fleeting ́⁰₃ that make an exit toward atopia.
[1]. Apolitics and Politics -- [2]. Liveable Interruption -- [3]. Forms of Experience.
Originally published in French as: Le refus de la politique. Paris : Hermann, [2012]
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Translated from the French.
Keywords: Political science -- Philosophy; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Political science -- Philosophy; Politische Philosophie; Politik; Demokratie; Kritik; Verweigerung